High Acceptability of an Orally Dispersible Tablet Formulation by Children - Leonie Wagner-Hattler; Klara Kiene; Julia Bielicki; Marc Pfister; Maxim Puchkov; Jörg Huwyler (MDPI AG, 2021)
There is a high unmet medical need for child-appropriate oral dosage forms. The acceptability of a novel placebo orally dispersible tablet formulation (pODT) was therefore evaluated. Monolithic tablets contain an inorganic calcium carbonate/calcium phosphate carrier material as the main excipient. They were assessed in a cross-sectional acceptability study. The 40 child participants were between 2 to 5 years and 6 to 10 years old. One pODT with 5 mm diameter was administered to each participating child by placement on the tongue or into the buccal cavity. Parents were asked to complete a questionnaire together with the study personnel. The spontaneous reactions of the children were recorded. The ease of administration and children's acceptance of the tablet was rated by research staff on a 4-point acceptability scale and by parents on a 5-point Likert scale. The older subjects answered how they had liked the pODT by pointing to the appropriate face of a Facial Hedonic Scale. pODT had very high acceptability as 93% of parents, and all questioned children reported the formulation to be acceptable or very acceptable. Staff reported administering pODT in these children without problems. None of the children showed distress on receipt of pODT. We conclude that the proposed child-friendly dosage form provides a convenient option for oral drug administration and is expected to enhance drug-adherence in pediatric patients.